Exploration of coupled surface–subsurface hydrological model responses and challenges through catchment- and hillslope-scale examples - Paniconi, Claudio; Lauvernet, Claire; Rivard, Christine (Frontiers in Water, 2025)
Selected runs with a physics-based model of surface water–groundwater interactions are used to examine in detail some numerical challenges and surprising behaviors that result from discretization, nested solution schemes, coupling, boundary condition, and other factors. Regardless of the spatial scale of the model domain (field, hillslope, catchment, …), the processes that are simulated by this class of integrated models can exhibit widely varying dynamics within and across the different subsystems comprising the land surface, the unsaturated zone, and deep groundwater formations. The presence of heterogeneities, nonlinearities, and complex boundary conditions can exacerbate numerical difficulties in resolving exchange fluxes across subsystems and lead to unexpected or undesired results, including localized numerical oscillations and an upper bound on adaptive time stepping. The need for accurate tracking of surface–subsurface exchanges and for better control of aspect ratio and mesh distortion can also influence and constrain spatial and temporal discretization choices. Finally, model performance assessments can be highly sensitive to the response variables of interest. We will illustrate some of these issues via test case simulations at large (13.66 km catchment transect) and small (450 m2 hillslope) spatial scales, run at time scales from 10 days to hundreds of years.